The Integration of Fintech and Artificial Intelligence: Accelerating Accountability and Financial Inclusion in National Financial Governance - Darmansyah Darmansyah; Arissetyanto Nugroho; Zulkifli Zulkifli; Winda Wulandari; Retna Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study investigates the role of Financial Technology (Fintech) and Artificial Intelligence (AI) in strengthening financial governance accountability and improving national financial inclusion. While prior studies have largely examined fintech and AI separately, this research develops an integrated model that positions accountability as a key mediating mechanism linking technological integration to broader financial inclusion outcomes. Using a quantitative explanatory design, data were collected through a digital survey involving 300 respondents consisting of public sector stakeholders, fintech actors, and users of digital financial services. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results reveal that fintech integration positively and significantly affects accountability and financial inclusion. Likewise, AI implementation significantly improves accountability and financial inclusion. Accountability also exerts a strong positive effect on financial inclusion. Mediation analysis shows that accountability partially mediates the effects of fintech and AI on financial inclusion. These findings suggest that the integration of fintech and AI contributes not only to operational efficiency but also to the improvement of governance quality and the expansion of inclusive financial access. The study contributes to the literature by proposing an integrative fintech, AI, accountability, financial inclusion framework in the context of a developing economy and offers evidence-based implications for policymakers and financial regulators.